Osteoarthritic changes rather than age predict outcome following arthroscopic treatment of femoroacetabular impingement in middle-aged patients. Issue 1 (December 2016) - Herrmann, Simon; Bernauer, Manuel; Erdle, Benjamin; Südkamp, Norbert; Helwig, Peter; Hauschild, Oliver
Abstract Background Our purpose was to evaluate outcome following arthroscopic treatment of femoroacetabular impingement (FAI) in middle-aged patients and to define risk factors for conversion to total hip arthroplasty (THA). Methods This was a retrospective case series of 79 consecutive patients (40 to 65 years) undergoing arthroscopic treatment of FAI (follow-up ≥12 months). Outcome at follow-up was assessed using Hip outcome score (HOS). Alpha angle, Kellgren Lawrence grade (K-L grade), joint space width (JS), lateral center edge (LCE) angle, caput-collum-diaphysis (CCD) angle and acetabular index (AI) were analysed retrospectively. THA group and Non-THA group were compared. Results Seventy-nine patients (mean age 48.6 years, mean follow-up 32 months) were included. 18 patients (22.8 %) were converted to THA. Mean HOS score in the Non-THA group at time point of follow-up was 80.2. Non-THA group and THA group showed no significant differences for mean age (48.2 years vs. 49.9 years, p = 0.278), alpha angel (p = 0.541), LCE (p = 0.294), CCD (p = 0.101) and AI (p = 0.661) in contrast to differences for JS (p = <0.001) and K-L grade (p = <0.001). Risk of conversion to THA was higher for patients with K-L grade 3 (p = 0.003) or joint space less or equal 2 mm (p = 0.001). Conclusions One fifth of the middle-aged patients required early conversion to THA. Advanced JS narrowing and K-L grade rather than age alone can be considered as risk factor for conversion to THA.